2021
DOI: 10.1016/j.cub.2021.08.032
|View full text |Cite
|
Sign up to set email alerts
|

A trail pheromone mediates the mutualism between ants and aphids

Abstract: A trail pheromone mediates the mutualism between ants and aphids Highlights d Mutualism with fire ants results in increased aphid population growth d Aphids perceive and respond to the trail pheromones of mutualistic fire ants d Ant trail pheromone components suppress dispersal in apterous aphids d Mutualistic aphids increase reproduction in response to ant trail pheromone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
0
13
1
1
Order By: Relevance
“…[ 72 ]. Although the α- and β-forms of farnesene are well-known pheromones [ 73 , 74 ], we did not find any reports on the biological activity of these compounds in human cells.…”
Section: Resultscontrasting
confidence: 70%
“…[ 72 ]. Although the α- and β-forms of farnesene are well-known pheromones [ 73 , 74 ], we did not find any reports on the biological activity of these compounds in human cells.…”
Section: Resultscontrasting
confidence: 70%
“…Additionally, tending ants might provide D. aberiae with other beneficial services such as transport to new feeding sites, 35 removal of excess honeydew, 36 and sanitization via removal of fungal contaminated‐individuals 37 . Furthermore, honeydew‐collecting ants can stimulate feeding and reproduction of some honeydew‐producing hemipteran species and reduce developmental times 38,39 . However, among the services that ants can provide to their trophobiont partners, the defence against natural enemies is the most important from a pest control perspective.…”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, honeydew-collecting ants can stimulate feeding and reproduction of some honeydew-producing hemipteran species and reduce developmental times. 38,39 However, among the services that ants can provide to their trophobiont partners, the defence against natural enemies is the most important from a pest control perspective. Tending ants often attack mealybug natural enemies, decreasing their efficacy as biological control agents.…”
Section: Discussionmentioning
confidence: 99%
“…Bioassay sample preparation. The trail pheromone fraction of hexane extract of 1 g of ant workers was prepared following the method in Xu et al (2021), which was then stored in a freezer at −20 °C for further bioassays.…”
Section: Identification Of Trail Pheromone Components In Ant Workersmentioning
confidence: 99%
“…Further laboratory bioassays confirmed multiple functions of the substances in the Dufour gland, including attracting workers and orienting them along trails (Wilson, 1962a, 1962b, 1962c). We recently found that components of S. invicta trail pheromone also mediate the ant's mutualism with aphids (Xu et al ., 2021). Regarding the chemical nature of the active substances in the Dufour gland, Barlin et al .…”
Section: Introductionmentioning
confidence: 99%